Financial Management Practices and the Performance of Micro Enterprises in Mukono Municipality - Derrick Kisakye (Uganda Christian University, 2025)
This research report established the connection between financial management practices and performance of micro-enterprises in Bugujju trading center in Mukono municipality. The report focused on the objectives; to investigate the influence of budgeting on the financial performance of micro enterprises, to examine the influence of cash flow management on the performance of micro enterprises, and to assess the effects of risk management on the performance of micro enterprises. It consists of the background information for this research, including the problem statement, objectives and purpose, research questions, the scope of the study, and its relevance in chapter 1. Chapter 2 displays an overview of the literature study on financial management techniques and the overall performance in micro enterprises and also how different researchers have evaluated these variables. Chapter 3 provides the research methodology that is to say the research design which was cross sectional research design, study population of 60, sample size of 50, data collection instruments which was a questionnaire, data quality (reliability and validity), and data presentation methods. Chapter 4 discusses the research findings in line with the research objectives. The study found out that success, profit, and business expansion can be attained by micro-enterprise through effective financial management practices. Proper financial management practices such as budgeting, cash flow management and risk management enable managers to predict future business needs and trends and also helping them respond to the financial status of the business at a given time. Data was provided in form of tables facilitate clarity and easy of interpretation.
Undergraduate